Enhanced Tailored MicroRNA Sponge Activity of RNA Pol II-Transcribed TuD Hairpins Relative to Ectopically Expressed ciRS7-Derived circRNAs - Anne Kruse Hollensen; Sofie Andersen; Karina Hjorth; Rasmus O. Bak; Thomas B. Hansen; Jørgen Kjems; Lars Aagaard; Christian Kroun Damgaard; Jacob Giehm Mikkelsen (Elsevier, 2018)
As key regulators of gene expression, microRNAs (miRNAs) have emerged as targets in basic experimentation and therapy. Administration of DNA-encoded RNA molecules, targeting miRNAs through base pairing, is one viable strategy for inhibiting specific miRNAs. A naturally occurring circular RNA (circRNA), ciRS-7, serving as a miRNA-7 (miR-7) sponge was recently identified. This has sparked tremendous interest in adapting circRNAs for suppressing miRNA function. In parallel, we and others have demonstrated efficacy of expressed anti-miRNA Tough Decoy (TuD) hairpins. To compare properties of such inhibitors, we express ciRS-7 and TuD-containing miRNA suppressor transcripts from identical vector formats adapted from RNA polymerase II-directed expression plasmids previously used for production of ciRS-7. In general, markedly higher levels of miR-7 suppression with TuD transcripts relative to ciRS-7 are observed, leading to superior miRNA sponge effects using expressed TuD hairpins. Notably however, we find that individual ciRS-7 transcripts are more potent inhibitors of miR-7 activity than individual TuD7-containing transcripts, although each miR-7 seed match target site in ciRS-7 is, on average, less potent than the perfectly matched target sites in the TuD motif. All together, our studies call for improved means of designing and producing circRNAs for customized miRNA targeting to match TuD hairpins for tailored miRNA suppression. Keywords: miRNA suppression, TuD, miRNA sponge, circular RNA, ciRS-7